"What Do You Mean It's Not Cancer?" A Review of Autoimmune and Systemic Inflammatory Diseases Involving the Breast. Issue 5 (28th May 2021) - Limninart, Narisara; Harvey, Jennifer A; Schultz, Katherine J; Mills, Anne M; Noland, Mary Margaret B; Schroen, Anneke T; Rochman, Carrie M
Abstract: Autoimmune and systemic inflammatory diseases represent a heterogeneous group of immune-mediated conditions with a wide range of clinical presentations and various affected organs. Autoimmune diseases can present in the breast as localized disease or as part of systemic involvement. Although breast involvement is uncommon, the spectrum of imaging findings can include breast masses, axillary adenopathy, calcifications, and skin changes, the appearance of which can mimic breast cancer. Common etiologies include diabetic mastopathy, systemic lupus erythematosus, scleroderma, rheumatoid arthritis, idiopathic granulomatous mastitis, sarcoidosis, and Immunoglobulin-G4 related mastopathy. This educational review will present multimodality imaging findings of breast manifestations of systemic inflammatory and autoimmune diseases and coexisting complications. It will also review how these disorders may affect breast cancer risk and breast cancer treatment options, including radiation therapy. Graphical Abstract: